Desempeño financiero de la Cooperativa de Ahorro y Crédito " 23 de Enero", del cantón Puyango, periodo 2022-2023 - Agila Agila, Ana Gabriela (2024)
Financial performance is a highly important factor for financial institutions. Its study is crucial for clients and partners of the entities to have full assurance of the actions of the entities. In the financial sector, this concept is a key point of analysis to ensure long-term sustainability. In this research, the financial performance of the Cooperativa de Ahorro y Crédito “23 de Enero” in the Puyango canton was analyzed for the 2022-2023 period. Therefore, it employed a mixed, non-experimental, exploratory, and descriptive approach. Moreover, it relied on bibliographic and deductive methods for information analysis. The collected data were cross-sectional, covering the period 2022-2023, with financial statements as the instruments presenting economic and financial information. The study unit was the Cooperativa de Ahorro y Crédito “23 de Enero,” located in the city of Alamor, Puyango canton. Through vertical and horizontal analysis, it was found that the credit union had a stable and well-balanced financial structure, meaning that half of its assets were financed by liabilities and the rest by equity. Furthermore, using the CAMEL methodology, it was noted that at least six financial indicators showed deficiencies, meaning their ratios did not meet the minimum standard, which increases financial risks for the institution. In summary, it was concluded that there is a need for the credit union’s directors to conduct regular financial analysis, including proportion analysis of financial accounts and their changes over time, as well as monitoring financial indicators through the CAMEL system, especially in asset quality and profitability, to improve the institution’s financial reality and, consequently, maximize its economic value through timely decision- making.